2014
DOI: 10.1007/s00296-014-3175-z
|View full text |Cite
|
Sign up to set email alerts
|

Potentially effective natural drugs in treatment for the most common rheumatic disorder: osteoarthritis

Abstract: Osteoarthritis (OA) is a chronic condition in which imbalance between anabolic and catabolic mediators occurs leading to the destruction of homeostasis of articular cartilage. The current drugs in the management of OA can just alleviate symptoms. Hence, the research tendency toward exploration of novel sources has been grown up in order to achieve safe and efficacious drugs. Meanwhile, various components exist as novel natural drugs that may possess favorable properties for the management of OA. This review fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…The significant decrease of total OHIP-14 values in group S and group P in comparison with group C may be attributed to the usage of topically applied pomegranates agents which enhanced collagen, DNA, and protein production along with improving contraction rate and tensile strength. As well as high levels of polyphenolic and tannin in the pomegranate extracts which accelerated wound healing through stimulation of production and movement of fibroblasts augmenting angiogenesis [27]. This is with an earlier clinical investigation which concluded that using pomegranate peel extract as a mouth wash was effective in decreasing pain and enhance wound healing in patients with RIOH [9].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The significant decrease of total OHIP-14 values in group S and group P in comparison with group C may be attributed to the usage of topically applied pomegranates agents which enhanced collagen, DNA, and protein production along with improving contraction rate and tensile strength. As well as high levels of polyphenolic and tannin in the pomegranate extracts which accelerated wound healing through stimulation of production and movement of fibroblasts augmenting angiogenesis [27]. This is with an earlier clinical investigation which concluded that using pomegranate peel extract as a mouth wash was effective in decreasing pain and enhance wound healing in patients with RIOH [9].…”
Section: Discussionmentioning
confidence: 63%
“…Numerous patients experienced several adversative reactions with this treatment option such as candidiasis and mucosal atrophy as formerly recognized [26]. Natural-origin drugs are considered to be safe and effective replacement therapy for many disorders [27]. As a result, the current study was conducted to assess the effectiveness of pharmaceutically prepared topical pomegranate extracts gel compared to commercially available topical steroid gel as a control in management of OLP concerning sign score, grade of pain and OHRQoL in this randomized clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional and folklore approaches for the management of diseases are among the main alternative sources of medicine. However, in spite of the growing level of tendency towards traditional medicine, evidence for safety and effectiveness of these alternative medicines is limited . Although conventional treatments of RA commonly alleviate the symptoms, high incidence of adverse reactions of these drugs has resulted in exploration of alternative methods, particularly traditional remedies, for symptomatic relief of RA.…”
Section: Discussionmentioning
confidence: 99%
“…This comprises antioxidant, antibacterial, antiviral, anti-allergic, anti-colitis, anti-inflammatory, anti-arthritic and anti-cancer activities [21][22][23][24][25] . Among several polyphenol sources in the human diet, tea is one of the most consumed beverages around the world as a result of the pleasant taste, attractive aroma and health-promoting effects.…”
Section: Health Benefits Of Tea Polyphenols As Dietary Natural Productsmentioning
confidence: 99%